2022
DOI: 10.3390/antiox11081621
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanism of Action of Melatonin, Which Induces ROS Production in Cancer Cells

Abstract: Reactive oxygen species (ROS) constitute a group of highly reactive molecules that have evolved as regulators of important signaling pathways. In this context, tumor cells have an altered redox balance compared to normal cells, which can be targeted as an antitumoral therapy by ROS levels and by decreasing the capacity of the antioxidant system, leading to programmed cell death. Melatonin is of particular importance in the development of innovative cancer treatments due to its oncostatic impact and lack of adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 93 publications
(125 reference statements)
2
22
0
Order By: Relevance
“…It should be stressed that melatonin can also act as a conditional pro-oxidant (acting only under special strictly defined conditions such as, e.g., cancerogenesis), especially in tumor cells and it is able to promote ROS generation at pharmacological concentrations [ 39 , 40 ]. However, this action of melatonin has been well-documented exclusively under in vitro conditions [ 41 ]. Beside this anticancer pro-oxidative action, which should be treated as a favorable effect, melatonin is able to suppress tumor growth, proliferation, and metastasis by mechanisms, such as induction of apoptosis, suppression of angiogenesis and tumor cell repopulation and stimulation of immune system cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be stressed that melatonin can also act as a conditional pro-oxidant (acting only under special strictly defined conditions such as, e.g., cancerogenesis), especially in tumor cells and it is able to promote ROS generation at pharmacological concentrations [ 39 , 40 ]. However, this action of melatonin has been well-documented exclusively under in vitro conditions [ 41 ]. Beside this anticancer pro-oxidative action, which should be treated as a favorable effect, melatonin is able to suppress tumor growth, proliferation, and metastasis by mechanisms, such as induction of apoptosis, suppression of angiogenesis and tumor cell repopulation and stimulation of immune system cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, quercetin treatment activated apoptosis in MCF-7 cells via the p38MAPK signaling pathway [ 112 ]. Kim et al [ 113 ] detected melatonin and its metabolites in honey, which possess strong free radical scavenging properties [ 114 ]. However, high concentrations of melatonin can induce the production of ROS, leading to apoptosis in a variety of cancers [ 115 , 116 , 117 ].…”
Section: Honey and Breast Cancermentioning
confidence: 99%
“…Melatonin, whose secretion is controlled by circadian rhythms, is a hormone synthesized and secreted mainly by the pineal gland 3 . Many studies have shown that melatonin can effectively inhibit all stages of cancer development and enhance the sensitivity of cancer cells to various anticancer drugs 4–6 . Melatonin is a pleiotropic anticancer molecule that regulates malignant cells via multiple mechanisms, including enhancement of mitochondrial reactive oxygen species, 7 targeting of Wnt/beta‐catenin signalling, 8 regulation of histone modification, 9,10 etc.…”
Section: Introductionmentioning
confidence: 99%